A New Efficient Dynamic System Information Scheduling Strategy in TDD-LTE - Zhiyuan Shi; Pingbo Chen; Lianfen Huang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The TDD-LTE system information which is also necessary to communicate each other well is a kind of important message between user equipment(UE) and eNodeB. Some important parameters are provided by system information to enable the UE to camp on a cell normally and access to common channel. The system information，of course，can provide the mobility management for UE in idle mode.  On the base station side, there are two kinds of scheduling methods of in the TDD-LTE system, and they are fixed scheduling and dynamic scheduling. The MasterInformationBlock (MIB) and the System Information Block Type1 use the fixed scheduling，while the dynamic scheduling is applied to other System Information Blocks (SIB2~SIB13); and these system information are transmitted on the Downlink Shared Channel(DL-SCH). In consideration of using the radio resources reasonably and not affecting other downlink transmitted data，we proposed a dynamic scheduling strategy of system information based on the base station side. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3309